Future's learning environments in health education: The effects of smart classrooms on the academic achievements of the students at health college - Sevindik, Tuncay (My University, 2010)
The aim of this study is to determine the effectiveness of smart classrooms on the academic achievement of the nursing students. The sample of the research included 66 Health College students in Elazi{dotless}?. The sampling group was randomly chosen from second year students of Nursing and Midwife Education. The research was carried out with experimental approach. The experimental group included nursing students and the control group, midwife students. Pre-test and post-test including questions regarding "internal diseases' course were applied to both groups. t-Test, percentage ands frequency were used as statistical procedures for data analysis. The findings showed that lectures given through smart classroom significantly increases the academic achievements of the students. It is, therefore, reasonable to state that smart classroom applications are effective environments that can be used as an alternative and a supplement to face to face educational environments in the institutions where health education is given. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Distance education; Smart classroom; Video conference